Intergenerational harmony : unleashing the strategic power of generational synergy - Yagnik, Arpan S. (Emerald points., 2024)
We find ourselves in a period of human history in which five generations coexist simultaneously. Not surprisingly, the success of any enterprise in any area of society is determined by the ability of individuals from different generations to collaborate productively. At the same time, intergenerational disharmony poses a range of risks including social conflict, educational imbalance, political discord, family fragmentation, religious decline and corporate inefficiency. While the composition of multiple generations within a team is a distinct asset, its potential is diminished by the absence of harmony between members of different generations. In Intergenerational Harmony: Unleashing the Strategic Power of Generational Synergy, author Arpan S. Yagnik delves into the concept of multigenerational coexistence, highlighting its impact on various sectors where multiple generations are navigating an evolving landscape. Across work, education, religion, government and family, the harmony between generations becomes a pivotal factor for long-term success. Addressing concerns such as resource and talent loss, Yagnik presents the concept of Intergenerational Harmony (IH), wherein generational stakeholders collaborate synergistically to harness their collective strengths. This practical guide offers insightful instances and examples of IH implementation, emphasizing empathy, respect, trust and honesty as its core values. By fostering IH, institutions can thrive in this era of multigenerational coexistence, countering challenges and paving the way for a harmonious future. Looking beyond generational labels and stereotypes to envision a harmonious, empathetic society, Yagnik pivots how we think about age and intergenerational relationships in every area and at every stage of our lives.